Design of target-variable spraying system based on FAVD of fruit tree canopy - Jiang, Shijie; Li, Wenwei; Ma, Hao; Wang, Kexin; Du, Zhe; Zheng, Yongjun (Frontiers in Plant Science, 2025)
IntroductionUsing air-assisted sprayer for chemical pesticide application is the main method for controlling pests and diseases in orchards. Target-variable spray based on canopy characteristics is an effective means to solve the problems of over-spraying, excessive residues, and environmental pollution.MethodsFoliage area volume density (FAVD), as it represents the number of pesticide targets in the canopy, can be used as a decision condition for variable spraying. Based on the previous FAVD detection method, this study developed a small target-variable sprayer based on FAVD, constructed a FAVD-spray rate control model, and conducted orchard experiments.ResultsThe experiment results showed that the targeted variable spray (TV) mode significantly improved deposition uniformity, and reduced ground loss and water consumption. For the TV model, the longitudinal variation coefficient was 11.42%, and the lateral variation coefficients were 55.27% (top layer), 58.80% (middle layer), and 43.15% (bottom layer), respectively. For the NTIV model, the longitudinal variation coefficient is 32.15%, and the lateral variation coefficients were 96.19% (top layer), 62.69% (middle layer) and 57.19% (bottom layer) respectively. In terms of ground and behind-canopy losses, the TV model reduced 79.78% and 73.54%, respectively, and saved 64.50% of water consumption.DiscussionCompared with the NTIV model, the TV model has small longitudinal and lateral coefficients of variation, the loss of droplets on the ground and behind-canopy is greatly improved, and it can significantly reduce the amount of water consumption. Target variable spraying based on FAVD can significantly improve the uniformity of droplet distribution in the canopy, reduce ground loss and environmental pollution, and provide a reference for the development of precision spraying technology in orchards.